ERG-Associated lncRNA (ERGAL) Promotes the Stability and Integrity of Vascular Endothelial Barrier During Dengue Viral Infection via Interaction With miR-183-5p - Zheng, Baojia; Wang, Hui; Cui, Guohui; Guo, Qianfang; Si, Lulu; Yan, Huijun; Fang, Danyun; Jiang, Lifang; Jiang, Zhenyou; Zhou, Junmei (Frontiers in Cellular and Infection Microbiology, 2020)
Dengue virus (DENV) continues to be a major public health problem. DENV infection will cause mild dengue and severe dengue. Severe dengue is clinically manifested as serious complications, including dengue hemorrhagic fever and/or dengue shock syndrome (DHF/DSS), which is mainly characterized by vascular leakage. Currently, the pathogenesis of severe dengue is not elucidated thoroughly, and there are no known therapeutic targets for controlling the disease effectively. This study aimed to further reveal the potential molecular mechanism of severe dengue. In this study, the long non-coding RNA, ERG-associated lncRNA (lncRNA-ERGAL), was activated and significantly up-regulated in DENV-infected vascular endothelial cells. After knockdown of lncRNA-ERGAL, the expression of ERG, VE-cadherin, and claudin-5 was repressed; besides, cell apoptosis was enhanced, and cytoskeletal remodeling was disordered, leading to instability and increased permeability of vascular endothelial barrier during DENV infection. Fluorescence in situ hybridization (FISH) assay showed lncRNA-ERGAL to be mainly expressed in the cytoplasm. Moreover, the expression of miR-183-5p was found to increase during DENV infection and revealed to regulate ERG, junction-associated proteins, and the cytoskeletal structure after overexpression and knockdown. Then, ERGAL was confirmed to interact with miR-183-5p by luciferase reporter assay. Collectively, ERGAL acted as a miRNA sponge that can promote stability and integrity of vascular endothelial barrier during DENV infection via binding to miR-183-5p, thus revealing the potential molecular mechanism of severe dengue and providing a foundation for a promising clinical target in the future.